fnh2004
contestada

PLAESE HELP

Two sets of equatic expressions are shown below in various forms:

Line 1: x2 − x − 6 (x + 2)(x − 3) (x + 0.5)2 − 6.25
Line 2: x2 − x − 2 (x + 1)(x − 2) (x − 0.5)2 − 2.25

Which line contains three equivalent expressions?
Line 1 only
Line 2 only
Both Line 1 and Line 2
Neither Line 1 nor Line 2

Respuesta :


Ok well let's start with line 1:

(x + 2)(x - 3) = x^2 - x - 6 (this works so far)
(x + 0.5)^2 - 6.25 = x^2 + x + 0.25 - 6.25
= x^2 + x - 6 (this is not equal to x^2 - x - 6 so Line 1 is not an answer)

Now for line 2:


(x + 1)(x - 2) = x^2 - x - 2 (this works so far)
(x - 0.5)^2 - 2.25 = x^2 - x + 0.25 - 2.25
= x^2 - x - 2 (this also works)
Therefor Line 2 only is the answer

Hey there!

I took the test, and I can confirm that B. Line 2 only is the CORRECT answer

xXxGolferGirlxXx